Geographic Information System (GIS) in Mapping Divorce-Prone Areas: Implications for Family Education Policy - Tohet, Moch; Sunarto, Muhammad Zainuddin (Universitas Nurul Jadid, 2024)
This study examines the use of Geographic Information System (GIS) in mapping divorce-prone areas and its implications for family education policy. Using a qualitative approach, this study used interviews, observations, and documentation to collect data. The results showed that GIS effectively maps areas with high divorce rates, which are influenced by factors such as education, economy, and age of marriage. GIS in family education policy allows for more targeted interventions, such as economic empowerment programs in areas with economic and education problems and communication training in areas with high divorce rates due to relationship problems. These findings strengthen the existing literature on the importance of geographic data-based policies to address social problems but also indicate the need for increased socialization to increase public acceptance.